A systematic approach to prioritizing R&D projects based on customer-perceived value using opinion mining. (December 2020) - Yoon, Byungun; Jeong, Yujin; Lee, Keeeun; Lee, Sungjoo
Abstract: As product development has recently emphasized user innovation, it should necessarily reflect customer-perceived value, as well as technological value itself. However, while previous studies for technology planning have focused on analyzing the potential of technology, they have not considered the customer-perceived value that technology can create in a new product. Therefore, this research suggests a new approach to assessing the level of technology and evaluating R&D projects, by investigating customer-perceived value on technology through the use of the structural equation model and opinion mining. For this, the assessment framework is developed in terms of technology, product quality, and customer satisfaction, respectively, by investigating a variety of databases on each factor. The relationship between technology level and customer satisfaction is analyzed, using structural equation model and opinion mining. Based on the results, a strategy for technology development is established through gap analysis and simulation, after selecting and evaluating technologies that need to be developed. The proposed approach is applied to the real case of a moving system, in particular an automobile door, and we obtained that an R&D project for hinge-related technology would be promising, enhancing the customer satisfaction. It can suggest a future direction for new technology development. This paper contributes to enhancing the efficiency of technology planning based on the customer-perceived value, enabling the launch of new R&D projects. Highlights: This paper proposes a new approach to assessing the level of technology and prioritizing R&D projects. The proposed approach investigates customer-perceived value through use of the structural equation model and opinion mining. Relations between technology, product quality, and customer satisfaction are analyzed by using a diversity of databases. The strategy for technology development is established through gap analysis and simulation. A real case of automobile doors is illustrated to show the validity of the proposed approach.